Factors that influence researchers' state of anomie in the research data sharing process - Monteiro, Elizabete Cristina de Souza de Aguiar [UNESP] (2022)
The low adherence between the perception and practice of established norms and the actions of researchers in the data sharing process results in a state of anomie that constitutes an important barrier to accessing data. It is assumed that there are standards, but that they are not followed in accordance with what has been established. The purpose of this text is to present and discuss factors that can influence researchers' state of anomie in data sharing. To achieve the objective, a framework with the factors that influence the perception and attitude of researchers in data sharing is presented. Documentary and exploratory research using the method of content analysis and application of the institutional theory, the theory of planned behavior and the research model for data sharing behaviors. The data revealed that indicators of the Cognitive, Normative, Career, Resources and Social pillars influence the perception and attitude of sharing or retain data. It is hoped that the results will allow a perception of the factors that influence researchers to share their data.